2009
DOI: 10.2527/jas.2008-1469
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ractopamine-hydrochloride on the fiber type distribution and shelf-life of six muscles of steers

Abstract: The goal of this study was to evaluate the effects of ractopamine-hydrochloride (RAC) supplementation on the myosin heavy chain isoform distribution and shelf-life properties of muscles from beef top round, knuckle, and loin. Thirty-four steer carcasses were selected from 4 separate slaughter groups. Within each slaughter group (3 groups, n = 8; 1 group, n = 10), steers were separated into pens (n = 8) and fed 0 or 200 mg x animal(-1) x d(-1) of RAC for the final 28 d of feeding. Seventy-two hours postmortem, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 20 publications
2
24
0
3
Order By: Relevance
“…The mechanism by which RAC increases longissimus area in our experiment could be interconnected with its ability to alter the metabolic profile of the individual fibres (Gonzalez et al, 2009). In agreement with these researchers, in the current study, RAC supplementation did not affect the colour characteristics in the longissimus.…”
Section: Discussionsupporting
confidence: 80%
“…The mechanism by which RAC increases longissimus area in our experiment could be interconnected with its ability to alter the metabolic profile of the individual fibres (Gonzalez et al, 2009). In agreement with these researchers, in the current study, RAC supplementation did not affect the colour characteristics in the longissimus.…”
Section: Discussionsupporting
confidence: 80%
“…Firstly higher driploss could increase surface moisture resulting in higher reflectance by the aqueous layer as reported by Geesink et al (1993). In addition, the shift towards whiter glycolytic fibre types and hypertrophy of these fibres caused by betaagonisttreatment (Gonzalez et al, 2009, Strydom et al, 2009 and Vestergaard, Henckel, Oksbjerg and Sejrsen, 1994 Wheeler & Koohmaraie, 1997) would have reduced the heme iron pigment concentration and hence result in paler meat (Geesink et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly higher driploss could increase surface moisture resulting in higher reflectance by the aqueous layer as reported by Geesink et al (1993). In addition, the shift towards whiter glycolytic fibre types and hypertrophy of these fibres caused by betaagonisttreatment (Gonzalez et al, 2009, Strydom et al, 2009 and Vestergaard, Henckel, Oksbjerg and Sejrsen, 1994 Wheeler & Koohmaraie, 1997) would have reduced the heme iron pigment concentration and hence result in paler meat (Geesink et al, 1993).Certain vitaminD 3 treatments reduced the effect of the beta-agonist on lightness for both fresh and aged meat. In fresh samples, 6D7M7N, and to some extent 3D7M were closer to those of the control but still significantly higher (P < 0.05), but in aged meat the effects of both treatments were more pronounced.…”
mentioning
confidence: 94%
“…Ractopamine hydrochloride has a direct effect on individual muscle fibers, causing type-I slowtwitch muscle fibers to transition to type-II fast twitch muscle fibers (Aalhus et al, 1992;Gonzalez et al, 2009). Gonzalez et al (2009) …”
Section: Beta-adrenergic Agonistsmentioning
confidence: 99%
“…The researchers found no other differences in carcass traits measured in experiment 2. Gonzalez et al (2009) evaluated the effect of RAC on shelf-life of steaks from the longissimus lumborum, semimembranosus, adductor, gracilis, vastus lateralis, and rectus femoris after being wet aged at 1 ± 2°C for 13 d. Steaks were evaluated subjectively by a trained panel over a 5-d simulated retail display study and objectively using a Hunter-Lab MiniScan XE. The researchers found that RAC had no effect on objective color measurements (P > 0.05); however, RAC tended to have a detrimental effect on subjective evaluations of lean color and surface discoloration scores of steaks from the vastus lateralis the last 3 d of the display (P < 0.10).…”
Section: Beta-adrenergic Agonists In Ruminantsmentioning
confidence: 99%